KEPENTINGAN AUSTRIA MENOLAK MENGUSIR DIPLOMAT RUSIA PASCA INSIDEN PERACUNAN AGEN RUSIA SERGEI SKRIPAL DI TAHUN 2018 - Poetry, Nabila Zelicha; Dharmiasih, D.A Wiwik; Suwecawangsa, Adi P. (Program Studi Hubungan Internasional FISIP Universitas Udayana, 2019)
ABSTRACT This research outlines the interests of Austria refusing to expel Russian diplomats from his country due to the Segrei Skripal poisoning incident. After Russia was suspected as the culprit behind the Sergei Skripal poisoning incident, Western countries condemned and expelled Russian diplomats from their respective countries. However, Austria as a member of the European Union became one of the countries that refused to follow that step. Austria's interest in not expelling Russian diplomats from its country is interesting to examine not only from the country's neutral position, but also the relationship between Austria and Russia. This study uses the Concept of Neutrality and National Interest Foreign Policy. The research methodology used is descriptive qualitative data obtained by literature review. The researcher argues that neutrality is not only the reason for Austria's policy of rejecting Russian diplomats from its country, but the country's political and economic interests with Russia. Keywords: Austria, Foreign Policy, Neutrality, National Interest, Political, Economic